Why Students Stay: Unpacking the Psychological Drivers of E-Learning Continuance Intention - Fitra Jaya; Siti Aisyah; Amalia Sapriati; Romi Siswanto; Yati Yati (Yayasan Keluarga Guru Mandiri, 2026)
Understanding what drives students to continue using e-learning platforms is critical for sustainable digital education. This study examines the mediating roles of cognitive presence and learning satisfaction in the relationship between e-learning quality dimensions and continuance intention. A survey of 447 undergraduate students from Universitas Terbuka Indonesia was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that cognitive presence and learning satisfaction significantly mediate the effects of information quality, instructor quality, system quality, and support service quality on continuance intention. While information and instructor quality positively influence engagement, their direct effects on continued use are limited. Conversely, system and support service quality impact learning indirectly through cognitive and affective mechanisms. These results suggest that students remain engaged not solely because of technical infrastructure but also because of meaningful, satisfying learning experiences. This study extends the Expectation Confirmation Model and e-learning quality frameworks by integrating cognitive presence as a central explanatory mechanism, offering a more student-centered theoretical understanding of continuance intention in digital higher education.